2006
DOI: 10.1111/j.1471-4159.2005.03583.x
|View full text |Cite
|
Sign up to set email alerts
|

O6‐methylguanine DNA methyltransferase and p53 status predict temozolomide sensitivity in human malignant glioma cells

Abstract: Temozolomide (TMZ) is a methylating agent which prolongs survival when administered during and after radiotherapy in the first-line treatment of glioblastoma and which also has significant activity in recurrent disease. O 6 -methylguanine DNA methyltransferase (MGMT) is a DNA repair enzyme attributed a role in cancer cell resistance to O 6 -alkylating agent-based chemotherapy. Using a panel of 12 human glioma cell lines, we here defined the sensitivity to TMZ in acute cytotoxicity and clonogenic survival assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
256
2
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 298 publications
(292 citation statements)
references
References 50 publications
24
256
2
10
Order By: Relevance
“…Similarly, p53 was shown to function as a survival factor in the gastrointestinal tract under conditions of severe irradiation, which was attributed to increased sensitivity of vascular endothelial cells (Komarova et al, 2004;Burdelya et al, 2006). Furthermore, other reports have identified conditions in which absence of p53 led to elevated apoptosis, but a direct causal role for p53 in providing survival signals has not been described (Lassus et al, 1996;Lackinger and Kaina, 2000;Hermisson et al, 2006;Batista et al, 2007;Roepke et al, 2007;Roos et al, 2007). Notwithstanding these occasional reports, the major observations that p53 activation often leads to apoptosis or DNA repair have been overwhelming, and hence, have overshadowed the exploration of the survival-promoting properties of p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, p53 was shown to function as a survival factor in the gastrointestinal tract under conditions of severe irradiation, which was attributed to increased sensitivity of vascular endothelial cells (Komarova et al, 2004;Burdelya et al, 2006). Furthermore, other reports have identified conditions in which absence of p53 led to elevated apoptosis, but a direct causal role for p53 in providing survival signals has not been described (Lassus et al, 1996;Lackinger and Kaina, 2000;Hermisson et al, 2006;Batista et al, 2007;Roepke et al, 2007;Roos et al, 2007). Notwithstanding these occasional reports, the major observations that p53 activation often leads to apoptosis or DNA repair have been overwhelming, and hence, have overshadowed the exploration of the survival-promoting properties of p53.…”
Section: Discussionmentioning
confidence: 99%
“…For example, absence of p53 has been shown to promote taxol-mediated death owing to failure of cell arrest in the G 1 phase of the cell cycle, and hence, allowing cells to accumulate in the G 2 /M phase where they undergo mitotic cell death (Vikhanskaya et al, 1998). In addition, cells with wild-type p53 have been shown to be more resistant to cytotoxic drug treatment in some cases (Hermisson et al, 2006;Batista et al, 2007;Roos et al, 2007). Other reports have also shown that absence of p53 leads to sensitization to UV irradiation and alkalyting agents in mouse embryonic fibroblasts (MEFs), and to thymoquinone-induced apoptosis in human cells (Lackinger and Kaina, 2000;Roepke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Neither dexamethsone nor irradiation induced MGMT gene transcription in glioma cells in vitro. 68 In tissue culture and animal studies, however, temozolomide strongly induced MGMT protein expression in temozolomide-resistant glioma cells lacking MGMT promoter methylation. 69 Loss of MGMT promoter methylation might represent a key mechanism by which patients with initially methylated tumors eventually acquire resistance to temozolomide, leading to progression or relapse.…”
Section: A Role For Routine Mgmt Testing?mentioning
confidence: 99%
“…For assessment of TMZ concentrations and doses of radiation the protocol of Hermisson et al (2006) was adapted. Cytotoxicity assays were done afterwards to optimize the doses for Hs683 cells (data not shown).…”
Section: Irradiation and Tmz Treatmentmentioning
confidence: 99%